Use of an eco-friendly anaesthetic in the handling of Puntius denisonii (Day, 1865) - an endemic ornamental barb of the Western Ghats of India - Sajan, S.; Malika, V.; Anna Mercy, T.V. (Indian Journal of Fisheries, 2012)
Anaesthesia is essential to minimise stress and physical damage while handling live fish. Present study evaluated theefficacy of clove oil as an anaesthetic (at four different concentrations viz., 20 mg l-1, 30 mg l-1, 40 mg l-1 and 50 mg l-1) forhandling the endemic ornamental barb Puntius denisonii. The onset of individual phases of anaesthesia and recovery rateswere studied. Induction time decreased with increasing concentration. Concentration between 30-40 mg l-1 of clove oil wasfound to be the most effective dose for P. denisonii and 30 mg l-1 was recorded as the lowest concentration that inducesanaesthesia in less than 3 min. Clove oil appears to be highly effective as a fish anaesthetic with potentially no side effects,which is safe for both fish as well as human and also less expensive.